Proposed regional plan for the implementation of the Luxembourg recommendations (ECLAC [Santiago]CL, 2008)
Describes the design of a regional strategy to support the implementation in the countries of Latin America and the Caribbean of the system of National Accounts 2008.
Keywords: STATISTICAL SERVICES